Application of electrode-driven shear flows for improved plasma confinement - Beklemishev, A.D.; Bagryansky, P.A.; Prikhodko, V.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
In open magnetic configurations (open traps, SOL) it is possible to control the plasma potential along magnetic field lines via external electrodes. This is a possibility for direct drive of shear flows and suppression of instabilities if there is a sufficient electrical contact of plasma with electrodes (such contact occurs across the Debye sheath and is not particularly good even in 100eV plasmas). In contrast to the ITB shear flows, the governing equations in this case are strongly dissipative: the same electrical contact (line-tying) that allows control of the plasma potential negates conservation of energy and enstrophy for long-wavelength perturbations. Thus, the electrode-driven shear flows are not particularly good for simulation of ITB physics. We show that nevertheless they can allow achievement of improved-confinement regimes in open traps. Due to their dissipative nature the generated flow layers possess structural stability that can be used for fast saturation of flute modes of different origin. Theoretical analysis is compared with experimental data from the gasdynamic trap in Novosibirsk, the GDT.